Layanan Bimbingan Konseling Karir Siswa Tunadaksa Kelas XI di SLB Samudra Lavender Kabupaten Bangkalan - Dewi, Shelly Kusuma; Sartinah, Endang Pudjiastuti (GRAB KIDS: Journal of Special Education Need, 2023)
One of the problems faced by students with disabilities is career. The existence of career counseling guidance will greatly help the rest of the disabled to be able to get motivation and direction in realizing their careers in the future. The role of teachers, counselors, and parents is indispensable to support the confidence of deaf students.  The purpose of this study was to describe the implementation of a career counseling guidance program for class XI blind students at SLB Samudra Lavender, Bangkalan district. This research is a type of descriptive research. Data collection techniques through observation, interviews and documentation. The data sources from this study consisted of guidance and counseling teachers (BK), special accompanying teachers (GPK) and students with disabilities. From the results of the study, it was obtained that the implementation of the career counseling guidance program for class XI blind students at SLB Samudra Lavender has gone well. This can be seen from the curriculum used is the modified 2013 curriculum. The modified 2013 curriculum is a curriculum that has been adapted to the Physically Handicapped students. An obstacle that often occurs in students with disabilities is the lack of self-confidence caused by limited physical functioning.   Keywords: guidance and counseling, career, physically handicapped student